The role of parents in instilling the values of early childhood education according to the Qur'an - Samsul Fajeri; Husin; Aulia Sani; Abdul Rashid bin Abdul Aziz (International Forum of Researchers and Lecturers, 2022)
Children are a gift from Allah SWT that should be grateful for, guarded, cared for, guided, educated and must also develop all their potential according to their nature. Education for children has got the most important place, because education is a very important factor in changing a civilization. This study aims to improve the role of parents in educating their children according to religious demands based on the Qur'an so that what is expected by parents can be applied to their children in living life. So this research is a library research. In this research will be explored about Early Childhood Education according to the Qur'an in the study of maudhu'i interpretation. Data were collected from various literatures, such as books, the Koran, interpretations and other research results are then processed into informative data. The results of this study indicate that the active role of parents in educating children is very much needed. Negligence of parents in educating children from an early age can result in unfavorable children's behavior in the future. Children's education according to the Qur'an shows how good children's behavior is, about what is the sense of responsibility for moral development in children, responsibility for attitudes towards children, responsibility for social development in children, responsibility for fostering prayer in children.